Production Systems, Human Resources and Employment Relations in Korea: The Case of Kia Motors - Lansbury, Russell D.; Woo, Seog-hun (Philippine Journal of Labor and Industrial Relations; Vol 21 (2001): Philippine Journal of Labor and Industrial Relations, 2021)
No abstract